Molecular Docking of the Bioactive Compound Physalis angulata as an Activator of Superoxide Dismutase 1 - Wilujeng, Retno; Harlina, Eva; Purwono, Rini Madyastuti; Andrianto, Dimas (Universitas Djuanda, 2025)
Physalis angulata was known for its pharmacological potential, including antioxidant activity, yet the specific bioactive compounds responsible for enhancing endogenous antioxidant enzymes, such as superoxide dismutase 1 (SOD 1), remained unclear. This study aimed to identify and evaluate the active compounds of P. angulata as natural SOD 1 activators using an In silico molecular docking approach. Forty-nine ligands derived from the active constituents of P. angulata were screened based on Lipinski’s Rule of Five and ADMET properties. Molecular docking was performed using the SOD 1 protein (PDB ID: 5YTO), and docking validation yielded an RMSD value of 0.005 Å. Among the test ligands, withanolide exhibited the most favorable binding energy (−7.011 kcal/mol) and the lowest inhibition constant (7.0 pM), forming strong interactions with key catalytic residues of the enzyme. These findings indicated that withanolide had promising potential as a natural SOD 1 activator, providing a basis for future antioxidant drug discovery.